Maths Formulas for Class 9

Most of the students of class 9 consider Mathematics subject as a nightmare and maths formulas for class 9 even more difficult to remember. This negative attitude towards one of the major subjects in every field makes them reluctant and lose interest from studies. Many get nervous just before exams and develops a feeling of insecurity. To stay away from this kind of problems, Byju’s brings you class 9 maths formulas pdf and formula list from NCERT books for class 9.

Maths Chart for Class 9

When you are clear with the logic behind every formulas and problem, solving any kind of problem is a lot easier. If you are perfect with all the below-mentioned formulas in Maths Chart for Class 9 that is listed chapter-wise, we assure you that nothing can stop you from scoring maximum marks in class 9 Mathematics examination.

Geometry Shapes Formulas for Class 9
Geometric Figure Area Perimeter
Rectangle A= l × w P = 2 × (l+w )
Triangle A = (1⁄2) × b × h P = a + b + c
Trapezoid A = (1⁄2) × h × (b1+ b2) P = a + b + c + d
Parallelogram A = b × h P = 2 (b + h)
Circle A = π r2 C = 2 π r
Algebraic Identities For Class 9
\((a+b)^{2}=a^2+2ab+b^{2}\)
\((a-b)^{2}=a^{2}-2ab+b^{2}\)
\(\left (a + b \right ) \left (a – b \right ) = a^{2} – b^{2}\)
\(\left (x + a \right )\left (x + b \right ) = x^{2} + \left (a + b \right )x + ab\)
\(\left (x + a \right )\left (x – b \right ) = x^{2} + \left (a – b \right )x – ab\)
\(\left (x – a \right )\left (x + b \right ) = x^{2} + \left (b – a \right )x – ab\)
\(\left (x – a \right )\left (x – b \right ) = x^{2} – \left (a + b \right )x + ab\)
\(\left (a + b \right )^{3} = a^{3} + b^{3} + 3ab\left (a + b \right )\)
\(\left (a – b \right )^{3} = a^{3} – b^{3} – 3ab\left (a – b \right )\)
\( (x + y + z)^{2} = x^{2} + y^{2} + z^{2} + 2xy + 2yz + 2xz\)
\( (x + y – z)^{2} = x^{2} + y^{2} + z^{2} + 2xy – 2yz – 2xz\)
\( (x – y + z)^{2} = x^{2} + y^{2} + z^{2} – 2xy – 2yz + 2xz\)
\( (x – y – z)^{2} = x^{2} + y^{2} + z^{2} – 2xy + 2yz – 2xz\)
\( x^{3} + y^{3} + z^{3} – 3xyz = (x + y + z)(x^{2} + y^{2} + z^{2} – xy – yz -xz\)
\( x^{2} + y^{2} = \frac{1}{2} \left [(x + y)^{2} + (x – y)^{2} \right ]\)
\( (x + a) (x + b) (x + c) = x^{3} + (a + b +c)x^{2} + (ab + bc + ca)x + abc\)
\( x^{3} + y^{3} = (x + y) (x^{2} – xy + y^{2})\)
\( x^{3} – y^{3} = (x – y) (x^{2} + xy + y^{2})\)
\( x^{2} + y^{2} + z^{2} -xy – yz – zx = \frac{1}{2} [(x-y)^{2} + (y-z)^{2} + (z-x)^{2}]\)<

Leave a Comment

Your email address will not be published. Required fields are marked *